International taxation in Canada: principles and practices - Li, Jinyan (LexisNexis, 2018)
The first comprehensive book on Canadian international tax law, International Taxation in Canada {u2013} Principles and Practices was originally published in 2006. Now in its fourth edition, it has become the leading book on this topic in Canada and is the most widely-adopted book for classroom usage at Canadian law schools. A unique and resourceful tool, it provides an understanding of the underlying policy governing international tax rules as well as how foreign tax laws interact with Canadian laws.